Role of Cord Blood Albumin and Bilirubin for Prediction of Significant Neonatal Jaundice - Gupta, Nidhi; Taran, Shachi Jain; Gupta, Surabhi; Arora, Kewal kishore (Journal of Nepal Paediatric Society, 2021)
Introduction: Nearly 60-80% of the term and preterm neonates are affected due to rise in bilirubin levels during early postnatal days, and causes readmission of the neonate sometimes with severe jaundice, which can be reduced if neonatal hyperbilirubinemia can be predicted early. The study was conducted to evaluate the predictive values of cord blood albumin and bilirubin for neonatal hyperbilirubinemia and to evaluate the better predictor between them. Method: In this hospital based observational study, 152 healthy term newborns with birth weight more than 2.5 kg were included. Assessment of cord blood haemoglobin, blood group, albumin and bilirubin levels was done. Follow-up for first consecutive five days after birth was done and assessed daily to look for evidence of jaundice, sepsis or any other illness. Serum bilirubin was evaluated at 72-96 hours of life in all neonates and was done early, if clinically indicated. Receiver’s Operating Characteristics curves were used for calculating the cut-off values of cord blood albumin and bilirubin in relation to hyperbilirubinemia. Result: The cut-off values obtained for albumin and bilirubin of cord blood was < 2.56 mg/dL and >2.33 mg/dL respectively at optimum sensitivity and specificity. Cord blood bilirubin was found to be highly sensitive for early recognition of significant neonatal hyperbilirubinemia as compared to cord blood albumin and can be used for screening purpose. Conclusion: Cord blood albumin and bilirubin can be used for negating the development of NNHB, but for screening purpose, cord blood bilirubin is more predictive of neonatal hyperbilirubinemia.